2022
DOI: 10.12968/jowc.2022.31.2.162
|View full text |Cite
|
Sign up to set email alerts
|

Antiseptic versus non-antiseptic solutions for preventing infection in acute traumatic wounds: a systematic review

Abstract: Objective: To compare the effectiveness of antiseptic solutions to that of non-antiseptic solutions in reducing wound infection rate, reducing bacterial load and improving wound healing. Method: We searched PubMed MEDLINE, Cochrane Central Register of Controlled Trials (CENTRAL), ProQuest Medical Database and medRxiv for randomised controlled trials (RCTs) comparing antiseptic solutions with non-antiseptic solutions in simple, uncomplicated acute traumatic wounds. Qualitative data synthesis was employed. Risk … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
1
0
0
Order By: Relevance
“…We observed that cleansers with antiseptic properties, including povidone‐iodine, led to a significantly greater reduction in bacterial FL area than non‐antiseptics and surfactants (saline, soap). This aligns with the findings from a 2022 systematic review focussed on antiseptic versus non‐antiseptic effectiveness in acute wounds, 26 however, that review only identified two RCTs that directly compared bacterial load reduction. We were unable to find any comparable reviews focused on chronic wounds, demonstrating the scarcity of rigorous, clinical evidence in this regard.…”
Section: Discussionsupporting
confidence: 72%
“…We observed that cleansers with antiseptic properties, including povidone‐iodine, led to a significantly greater reduction in bacterial FL area than non‐antiseptics and surfactants (saline, soap). This aligns with the findings from a 2022 systematic review focussed on antiseptic versus non‐antiseptic effectiveness in acute wounds, 26 however, that review only identified two RCTs that directly compared bacterial load reduction. We were unable to find any comparable reviews focused on chronic wounds, demonstrating the scarcity of rigorous, clinical evidence in this regard.…”
Section: Discussionsupporting
confidence: 72%